Overcoming life's sorrows: learning from Jeremiah - Lessing, R. Reed (Concordia Publishing House, 2021)
"This unique book is a combination of Bible commentary and devotional reflection, applying biblical truth to our lives and inviting readers to see how God uses His people's story in the Book of Jeremiah to speak to our difficult questions in the face of disaster. Anyone who has experienced a life-altering event will benefit from this resource"--